2017
DOI: 10.1016/j.apjtm.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Time-kill kinetics and biocidal effect of Euclea crispa leaf extracts against microbial membrane

Abstract: This study suggests the leaf of Euclea crispa a source of bioactive compound with membrane attack as one of the mechanisms of its biocidal action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…The maximum amount of proteins (0.566 µg/ml) was released from K. pneumoniae by an n-butanol fraction at 2×MIC after 120 min of treatment while the maximum amount of nucleotides released (4.575 µg) was from B. pumilus by n-hexane fraction under similar condition. Furthermore, membrane disruption has also been confirmed in the course of this study as one of the mechanisms of biocidal action of the leaf extract [81].…”
Section: Cell Membrane Disruptionsupporting
confidence: 72%
See 3 more Smart Citations
“…The maximum amount of proteins (0.566 µg/ml) was released from K. pneumoniae by an n-butanol fraction at 2×MIC after 120 min of treatment while the maximum amount of nucleotides released (4.575 µg) was from B. pumilus by n-hexane fraction under similar condition. Furthermore, membrane disruption has also been confirmed in the course of this study as one of the mechanisms of biocidal action of the leaf extract [81].…”
Section: Cell Membrane Disruptionsupporting
confidence: 72%
“…Hence, leaf extracts of E. crispa could be a good source of readily available drug against the aforementioned ailments in folklore remedy. The growth of E. coli, a common causative agent of diarrhea and urinary tract infections, and species of Salmonella and Shigella were also significantly inhibited by the extracts [81]. These findings validate traditional use of E. crispa as herbal medicine against antimicrobial infections.…”
Section: Antifungal Activitiessupporting
confidence: 61%
See 2 more Smart Citations
“…It is widespread and common in the interior regions of southern Africa. 6 This plant is used traditionally against wide range of ailments such as gonorrhea, leprosy, scabies, diarrhea and wound infections and previous reports have shown that the plant possessed anti-bacterial and antifungal activities. 7 Virtual screening based on computer-aided techniques are very promising in drug discovery and plays an important role in identifying lead compounds from natural products.…”
Section: Introductionmentioning
confidence: 99%